Dampak Fluktuasi Pendapatan pada Tingkat Penjualan di Perusahaan BTC Watampone dalam Perspektif Ekonomi Mikro Islam - Muhammad Faiz Haikal; Malika Aura Kinanti; Muhammad Rafly; Nadya Nur Haplah; Naufal Aziz Maulana; Mia Lasmi Wardiyah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Sales of goods and services are significantly impacted by fluctuations in the level of people's income. The community’s financial stability is crucial for the continuity of economic operations according to sharia principles in Islamic microeconomics. Islamic microeconomics does not only seek profit, but additionally aims to enhance the welfare of the people in a fair and sustainable manner. Because justice, brotherhood, and cooperation are elements that can offer options for fluctuations in human income. The object of this research is BTC Watampone. This study’s objective is to examine how changes in income impact the level of sales from an Islamic economic point of view. This study employs a literature review-based quantitative method, which relies on various library sources to gather the required information. The study’s findings indicate of this study show that the elasticity of sales volume in 2015 was Ep = 0.723, which indicates that Ep < 1 and sales volume is classified as inelastic. While the elasticity of sales volume in 2016 is Ep = 17.2, which indicates that Ep > 1 and sales volume is classified as elastic.